Measurement of Postmortem Pupil Size: A New Method with Excellent Reliability and Its Application to Pupil Changes in the Early Postmortem Period. Issue 3 (1st December 2016) - Fleischer, Luise; Sehner, Susanne; Gehl, Axel; Riemer, Martin; Raupach, Tobias; Anders, Sven
Abstract: Measurement of postmortem pupil width is a potential component of death time estimation. However, no standardized measurement method has been described. We analyzed a total of 71 digital images for pupil–iris ratio using the software ImageJ . Images were analyzed three times by four different examiners. In addition, serial images from 10 cases were taken between 2 and 50 h postmortem to detect spontaneous pupil changes. Intra‐ and inter‐rater reliability of the method was excellent (ICC > 0.95). The method is observer independent and yields consistent results, and images can be digitally stored and re‐evaluated. The method seems highly eligible for forensic and scientific purposes. While statistical analysis of spontaneous pupil changes revealed a significant polynomial of quartic degree for postmortem time ( p = 0.001), an obvious pattern was not detected. These results do not indicate suitability of spontaneous pupil changes for forensic death time estimation, as formerly suggested.